PEMBERDAYAAN KELOMPOK DASAWISMA PEDUSAN MELALUI PELATIHAN PEMBUATAN HIASAN RAJUTAN DI DUSUN PEDUSAN, SEDAYU, YOGYAKARTA - Barbara Gunawan (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Argosari Village is an area located next door to the northwest corner of Bantul Regency with an area of 628,4720 ha. Argosari Village is precisely located in Sedayu District, Bantul Regency, Yogyakarta Special Region Province. Padukuhan Pedusan is part of Argosari Village. Padukuhan Pedusan is one of the hamlets located in the Southeast of Padukuhan Sedayu. With an area of 41.66 ha. Administratively, padukuhan Pedusan area is divided into 4 Neighboring Pillars / RT. Rt 057, 058, 059, and 060. One of the Association of Mothers in Pedusan Hamlet, is Dasa Wisma which consists of Mothers from 10 houses. So far, Dasa Wisma Pedusan's activities are only arisan and save loans, when in fact if the association is managed properly, it can provide positive activities as well as produce. One of the positive activities offered to Dasa Wisma Pedusan mothers is knitted handicrafts and macrame, whose manufacturing process is relatively easy, can be done at home, and generates income that can improve the family economy. Currently, macrame crafts are in great demand by lovers of handicrafts. The problem faced by the Pedusan guesthouse decade to start activities is the absence of companion instructors, models that have not been diverse, and product marketing mechanisms. This service program is in the form of: 1) providing training and mentoring in making knitted and macrame, 2) training and product marketing assistance, and 3) Simple bookkeeping training and assistance. It is hoped that this activity will make the activities of the homestead decade more useful and generate additional income for members. After this activity, mothers and young women have produced products in the form of knitting and macrame that are useful, and in the routine activities of meetings always improve their proficiency. Participants hope that similar activities will always be held so that member skills will increase and can increase income.